Assessment, Analysis, Adjustment And Advancement Of The Human Resource And Motivational Excercises In The Ministry Of Domestic Trade And Consumer Affairs Of Malaysia (MOTCAM) - Shankaran, R. A/L L.R. Murthy (2006)
This thesis highlight and explain the purpose of the Ministry as an important regulator in the Malaysian economy. The aim of the thesis is to evaluate the human and social values, like psychological aspects, social influences, which, play a significant role in HR performance.